Integrated package for sustainable restoration of silvopasture production systems in Tunisia - CGIAR Research Program on Livestock (2020)
The experience and findings were presented during national tree week in Tunisia. The Directorate General of Forests started outscaling this innovation to other locations. More awareness was raised about indigenous forage legume species for restoration of degraded agropastoral sites. and an expert meeting on sulla conducted to enhance its use.